The Impact of Information & Communication Technology on Land Transportation Service Business on Indonesia (Case Study in Central Sulawesi Province) - Sutrisno K Djawa (International Journal Labs, 2023)
The development of information and communication technology (ICT) has an impact on the land transportation service business in Indonesia. ICT enables efficiency and effectiveness in business processes, but also has an impact on changing consumer behavior and competition between companies. Therefore, this study was conducted to determine the impact of ICT on land transportation service business in Indonesia. The purpose of this study is to determine the impact of ICT on the land transportation service business in Indonesia, both in terms of efficiency and effectiveness of business processes as well as in terms of changes in consumer behavior and competition between companies The research method used is a qualitative approach by conducting in-depth interviews with key speakers, observing the symptoms and phenomena of transportation flows, and conducting a rigorous literature review. The results obtained from this study are that the use of ICT in the land transportation service business in Indonesia has a positive impact on the efficiency and effectiveness of business processes, as well as has an impact on changing consumer behavior and competition between companies. In terms of efficiency and effectiveness, the use of ICT helps companies in increasing productivity and reducing operational costs. Meanwhile, in terms of changes in consumer behavior, the use of ICT allows online ordering and payment, making it easier for consumers to use land transportation services. The impact of ICT on competition between companies can be seen from the existence of new companies that emerge with different business models and are more innovative in using ICT.